2020
DOI: 10.1037/ebs0000178
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, victimization, and prosocial resource control strategies: Differential relations with dominance and alliance formation.

Abstract: Using evolutionary theories related to bullying, resource control, and reciprocal altruism as guiding frameworks, this study examined how bullying perpetration, bullying victimization, and prosocial resource control strategies were associated with two distinct indicators of the ability to acquire resources—dominance and alliance formation. Adolescents (N = 396; Mage = 14.64, SDage = 1.52; 58% girls) completed self-report measures on bullying perpetration and victimization, prosocial strategies, dominance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 54 publications
(177 reference statements)
0
32
0
Order By: Relevance
“…That is, these adolescents are helpful, cooperative, and concerned with obtaining and maintaining a positive peer‐group reputation (e.g., social preference), while at the same time striving for peer‐group harmony (i.e., getting along). Recently, adolescents' prosocial strategic behavior was found to be associated with the ability to acquire social resources through cooperative alliance formation (Farrell & Dane, 2020). The present findings regarding anti‐bullying adolescents' higher Honesty‐Humility—or their inclination toward proactive reciprocal altruism—support the hypothesis that adolescents may strategically use (direct) defending to form cooperative alliances with peers.…”
Section: Discussionmentioning
confidence: 99%
“…That is, these adolescents are helpful, cooperative, and concerned with obtaining and maintaining a positive peer‐group reputation (e.g., social preference), while at the same time striving for peer‐group harmony (i.e., getting along). Recently, adolescents' prosocial strategic behavior was found to be associated with the ability to acquire social resources through cooperative alliance formation (Farrell & Dane, 2020). The present findings regarding anti‐bullying adolescents' higher Honesty‐Humility—or their inclination toward proactive reciprocal altruism—support the hypothesis that adolescents may strategically use (direct) defending to form cooperative alliances with peers.…”
Section: Discussionmentioning
confidence: 99%
“…An agentic leadership orientation involves being dominant, assertive, competitive, active, decisive, and achievement orientated (Abele, 2003 ; Kark et al, 2012 ). Research suggests that dominance is associated with bullying perpetration (Farrell & Dane, 2020 ). Meanwhile, other studies have shown that highly competitive organizational environments may lead to increased incidences of workplace bullying (Cheng & Huang, 2019 ).…”
Section: The Moderating Effects Of Leadership Orientationmentioning
confidence: 99%
“…Finally, the economic recession could have also resulted in a higher risk for obtaining resources through parental investment in male adolescents. The final consequence is male adolescents’ need to take part in risk-taking behaviors to access such resources, something which has been demonstrated in bullying behaviors ( Volk et al, 2012 ; Farrell and Dane, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…From an adaptive perspective, we propose that adolescents who take part in risk-taking behaviors need to be viewed in a different manner in order to understand them. In fact, risk-taking behaviors such as bullying have been seen to increase access to resources, such as food, social status, and mates ( Volk et al, 2012 ; Farrell and Dane, 2020 ).…”
Section: Introductionmentioning
confidence: 99%